The rise of lone wolf terrorism-new challenge to media - Miloshevska, Tanja; Kirkova, Rina; Stojanoska Ivanova, Tatjana (Institute od knowledge management, Skopje, 2019)
Today, one of the most challenging and unpredictable forms of terrorism are violent terror acts committed by single individuals, often referred to as lone wolf terrorists or lone actor terrorists. One of the major problems with detecting possible lone wolf terrorists is that there is no consistent or typical profile.Lone wolf terrorists pose a large threat to modern society. The purpose of this paper will be focused on one of the most unpredictable forms of terrorism acts-those committed by a single individual, a so-called ”lone wolf terrorist”. The phenomenon of so-called lone wolf terrorism has increased with more and more attacks perpetrated by single actors.The shifting nature of terrorism has prompted a debate over how to accurately describe individuals that act independently of a terrorist organization’s chain of command.Lone-wolf terrorists’ acts are not only meant to inflict pain and death but also to spread terror and fear. They commit these crimes to catch the attention of the public and indeed of the state. Their expectations are that terrorizing nations will create pressure from the public and force states to amend their policies and subsequently meet their demands.The concept of the lone wolf terrorist is increasingly common in recent decades, often attracting media attention as a “new” and “dangerous” threat. Live television news events have been dominated by incidences involving lone-wolf terrorist attacks recently. This has presented new challenges to the broadcast news media.It is a growing phenomenon, but research on this topic has been accompanied by major shortcomings, because this type of violence may be one of the most mysterious and unforeseeable forms of terrorism. Therefore, the lone wolf concept needs to be reevaluated and adapted to changed circumstances.The current ability to identify and stop these kind of terrorists before they commit a terror act is limited since they are very hard to detect using traditional methods. However, these individuals often make use of Internet to spread their beliefs and opinions, and to obtain information and knowledge to plan an attack.Lone wolf terrorism has been considered as a serious threat to public security in recent years and an extremely difficult challenge for security-they are relatively unpredictable, undetectable and effectively unstoppable.The unique features of lone-actor terrorism, including the challenges of interdiction and potential of copycat attacks, mean that the media is likely to play a particularly important role in shaping the reactions of the public, affected communities and copycat attackers.Furthermore, socioeconomic approaches need to be adopted to tackle the phenomenon of terrorism from the roots because policing and counter-terrorism operations alone have proven to be insufficient.It means displaying interest, respect and appreciation for others’ linguistic, cultural and religious traditions.Currently, there are more questions than answers on the content and validity of the lone wolf concept, but we should be alert and aware that the external conditions have changed, and old responses may not be appropriate anymore to present-day lone actor terrorism.
Keywords: lone wolf terrorist, terrorist violence, media, communication, coverage